2018
DOI: 10.1177/0022146518790560
|View full text |Cite
|
Sign up to set email alerts
|

Marriage, Social Control, and Health Behavior: A Dyadic Analysis of Same-sex and Different-sex Couples

Abstract: Prior research based on studies of heterosexual populations suggests that men's health benefits more from marriage than women's, in part because women do more than men to influence the health habits of their spouse. We extend this work by using dyadic survey data from 838 spouses in 419 gay, lesbian, and heterosexual marriages to consider differences in social control tactics across same-sex and different-sex couples-that is, how spouses monitor and regulate each other's health habits. Results suggest that alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 44 publications
1
71
0
Order By: Relevance
“…This asymmetry may reflect the fact that wives feel a greater responsibility for and play a more intensive role in caring for ailing spouses than do husbands. However, comparative studies find that this partner inequality in spousal caregiving is more pronounced in heterosexual couples than same‐sex couples (Umberson et al, ). The burden of spousal care borne by women is more intense for those married to men than women, challenging the conflation of “male” and “female” with gendered caregiving roles, even among a cohort of older adults who had been socialized to comply with those role expectations (Salari & Zhang, ).…”
Section: Marriage and Romantic Partnershipsmentioning
confidence: 99%
See 1 more Smart Citation
“…This asymmetry may reflect the fact that wives feel a greater responsibility for and play a more intensive role in caring for ailing spouses than do husbands. However, comparative studies find that this partner inequality in spousal caregiving is more pronounced in heterosexual couples than same‐sex couples (Umberson et al, ). The burden of spousal care borne by women is more intense for those married to men than women, challenging the conflation of “male” and “female” with gendered caregiving roles, even among a cohort of older adults who had been socialized to comply with those role expectations (Salari & Zhang, ).…”
Section: Marriage and Romantic Partnershipsmentioning
confidence: 99%
“…Recent studies have explicated both biological and psychosocial mechanisms through which family relationships and intrafamilial exchanges protect or undermine older adults' well‐being (e.g., Donoho, Crimmins, & Seeman, ). Innovations during the past decade in the collection and analysis of biomarker, dyadic, family‐level, and social network data have enabled researchers to examine new aspects of perennial questions, such as the implications of marital dissolution and family caregiving for older adults' well‐being and timely new topics such as older adults' provision of spousal care in same‐sex versus heterosexual marriages (Umberson, Donnelly, & Pollitt, ). Harmonized cross‐national data resources, encompassing nations in Africa, Asia, Europe, Latin America, and North America, permit documentation of how policy and cultural contexts shape outcomes such as intergenerational exchanges and older adults' well‐being (Lee et al, ).…”
mentioning
confidence: 99%
“…Regarding contagion, social connections may model smoking behavior, sometimes initiating a process of smoking contagion that helps explain why those surrounded by smokers often start smoking and have difficulty quitting (Margolis & Wright, 2015). And finally, smoking is impacted by social control processes (i.e., attempts to monitor and regulate another's health behavior and internalization of norms and meanings that influence health behaviors), which can discourage smoking depending on the salience of those ties (Umberson, Donnelly, & Pollitt, 2018).…”
Section: Linked Lives and Smokingmentioning
confidence: 99%
“…Moreover, compared to men who lived alone, the study showed that men who were living with a partner adhered more regularly to the program [19]. This nding a rmed the in uence of heterosexual gender relations for promoting men's health in the context of living with prostate cancer [20]. Indeed, women have been socialized to care for the health of others', especially family and the men in their lives, while men are socialized to risk rather than promote their health [21].…”
Section: Introductionmentioning
confidence: 71%